Ritual Dalam Proses Pembuatan Perahu Pinisi - Wahyuni Wahyuni; Imam Sadik (SOSIORELIGIUS, 2022)
Abstract This paper presents the Ritual in the Process of Making a Phinisi Boat, which was obtained through primary sources of interviews with H. Galla Muhammad Sholeh and additional secondary data. Starting from the Phinisi background, influence, and impact in South Sulawesi. Starting from the Sawerigading twin brothers who wanted to have transportation at sea, and the manufacture of the phinisi boat started from the wreck of the Sawerigading boat which was stranded in three areas, namely Ara, Lemo-lemo and Bira. in the Land of Beru. Keywords: Tradition, Boat, Ritual